Cost-effectiveness of gestational diabetes screening in middle-income countries: a systematic review - Annisa, Pariqa; Br Karo, Deliana; Ratnaningrum, Asti; Samosir, Yohana; Astuti, Andari Wuri; Icanervilia, Ajeng Viska; De Moniz, Maria Fatima (Universitas Aisyiyah Yogyakarta, 2024)
The majority of GDM occurs in low- and middle-income countries. GDM is associated with increased maternal and infant complications as well as an increased burden of health financing. Accurate and cost-effective screening is needed for prevention and further treatment. Unfortunately, there is a lack of research on the cost-effectiveness of GDM screening in middle-income countries. The objective of this study was to uncover scientific proof concerning the cost-effectiveness analysis of screening for gestational diabetes in middle-income countries. We conducted a systematic review using Pubmed and ScienceDirect. Four reviewers screened the title and abstract of each article, followed by the selection of the full text based on the inclusion criteria (cost-effectiveness analysis studies of GDM screening and original research). Quality articles were assessed using the CHEC-Extended tool. A total search of 1239 articles found 3 studies that met the inclusion criteria. A screening program is more cost-effective than no screening, this represents a savings of 1,329,671. The ICER value is less than 3x GDP per capita, which indicates that the intervention is cost-effective. Compared to two-step screening, one-step screening is more likely to be cost-effective since it detects more cases. As the prevention of DALYs is mainly due to the prevention of T2DM, middle-income countries should focus more on postnatal care for women with GDM in the future. It is advised that long-term follow-up studies be a major focus of future research in order to evaluate the follow-up GDM screening intervention's possible long-term health benefits and financial effects.